ANALYSIS OF POLLUTION LOAD IN THE WELANG RIVER DOWNSTREAM BASED ON ORGANIC AND HEAVY METAL PARAMETERS - Widyastuti, Indri Ika; Al Hazman, Muhammad; Sukarno, Friska Intan (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2025)
To assess water pollution in the downstream of the Welang River, this research examines several key water quality indicators, including organic indicators (DO, COD, TSS) and selected toxic substances such as ammonia, chromium, and sulfide. Water samples were collected from four monitoring stations representing the estuarine zone and analyzed using the Pollution Index method in accordance with Government Regulation No. 22 of 2021. The results showed that DO levels varied between 3,6-4,2 mg/L, with COD levels reaching up to 25 mg/L, respectively. The highest level of TSS concentration was recorded at Station 4 (200 mg/L), while the highest ammonia level at Station 2 (1,38 mg/L). Chromium and sulfide levels varied between 0,015–0,031 mg/L and 0,0016–0,0029 mg/L. By integrating both organic and toxic parameters within a unified assessment framework, this approach offers a more detailed characterization of estuarine pollution—an area often underrepresented in national water quality monitoring programs. The analysis indicates that all stations are moderately to heavily polluted. These conditions are likely caused by a combination of domestic waste, agricultural runoff, and effluents from nearby industrial activities. These insights are intended to support better environmental planning and pollution control strategies, especially in coastal and estuarine zones under growing human pressure.